2014
DOI: 10.1007/s10840-014-9937-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulmonary vein isolation on atrial fibrillation recurrence after ablation of paroxysmal supraventricular tachycardia in patients with high dispersion of atrial refractoriness

Abstract: PVI addition after successful AP or slow pathway of atrioventricular node ablation significantly reduced AF recurrence in PSVT patients with high atrial vulnerability (dERP >74.5 ms).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…Our data showed that the AERP was clearly different among regions: longest in the HRA and shortest in the PCS. AER after AF leads to a decreased AERP and enhances its dispersion 30 . Due to electrical remodeling, the mean AERP was shorter in patients with persistent AF than in those with PAF 31 .…”
Section: Discussionmentioning
confidence: 95%
“…Our data showed that the AERP was clearly different among regions: longest in the HRA and shortest in the PCS. AER after AF leads to a decreased AERP and enhances its dispersion 30 . Due to electrical remodeling, the mean AERP was shorter in patients with persistent AF than in those with PAF 31 .…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies reported that the rate of AF remission was 9-42% with Kent bundle ablation alone [3,4,[7][8][9]. A recent study showed that the addition of PVI after successful ablation of paroxysmal supraventricular tachycardia (of which 29 were patients with Kent bundle) reduced the AF recurrence rate, but the difference did not reach a statistical significance (p = 0.20) [12]. Our results in 96 patients with Kent bundle were similar to theirs, strengthening the notion that PVI may not be necessary in all patients with WPW syndrome and AF.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, catheter ablation has been widely accepted as a treatment option for symptomatic paroxysmal AF [10] and in clinical practice, ablation of Kent bundle and AF are frequently performed during the same session [11]. However, few reports have assessed the efficacy of additional AF ablation in preventing residual AF in such patients, or its necessity [12].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is unknown whether additional PVI immediately after AP ablation effectively prevents AF recurrence in these patients. A recent study showed that adding PVI after successful ablation of paroxysmal supraventricular tachycardia (29 of the patients had APs) reduced the AF recurrence rate, but the difference did not reach statistical significance 19 . Kawabata et al 6 compared the efficacy of AP ablation alone and additional AF ablation on accompanying AF and found that adding PVI did not improve the freedom from residual AF compared with AP ablation alone in all patients with WPW syndrome and AF; however, adding PVI significantly reduced AF recurrence in a subgroup of patients with brain natriuretic peptide (BNP) concentrations >40 pg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that adding PVI after successful ablation of paroxysmal supraventricular tachycardia (29 of the patients had APs) reduced the AF recurrence rate, but the difference did not reach statistical significance. 19 Kawabata et al 6 Because several studies showed that age >50 years was an independent predictor of AF recurrence after AP ablation, 3,4,7,10 we examined the efficacy of additional PVI after AP ablation in preventing AF recurrence in these subgroup of patients, in the present study. We found that additional PVI did not significantly reduce AF recurrence in these patients.…”
Section: Discussionmentioning
confidence: 99%